UNDERSTANDING CRYPTO APPLICATION ACCEPTANCE THROUGH TECHNOLOGY ACCEPTANCE MODEL IN YOGYAKARTA - Taufan Adi Kurniawan; Anita Primastiwi; Devina Andriany; Mochamad Fariz Irianto (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
Crypto investors in Indonesia increased from 13.31 million in February 2025 to 13.71 million in March 2025, but the value of crypto transactions actually decreased from IDR 32.78 trillion in February 2025 to IDR 32.45 trillion in March 2025. This indicates that more Indonesians are interested in choosing crypto as an investment element, but on the other hand, the decline in the number of transactions indicates a hesitation or tendency to refrain from making transactions among the public. This is interesting because on the one hand, the number of crypto investors is increasing, indicating that society is beginning to accept crypto as an investment, despite their lack of literacy, and amidst various risks of crypto losses. Research shows that the risks of crypto investments are higher than those of stocks, and investors need adequate knowledge to invest. This study analyze factors that influence user acceptance of crypto applications by using the Technology Acceptance Model (TAM) by adding several external variables, namely subjective norms and perceived risk. This study uses Structural Equation Modeling Partial Least Square (SEM-PLS) method using random sampling, with Yogyakarta residents as a sample. The research results show that the two highest scores involve perceived ease of use variable. Uniquely, the two lowest scores involve perceived usefulness variable. Perceived risk variable shows a moderate value, indicating that a sufficient number of people understand the risks involved in crypto applications.